VARIASI SPASIO-TEMPORAL JENIS MAKANAN IKAN MOTAN, Thynnichthys polylepis DI RAWA BANJIRAN SUNGAI KAMPAR KIRI, RIAU [Spatio-temporal variation in the diet of Thynnichtys polylepis in floodplain river of Kampar Kiri, Riau] - Ahmad Zahid; M. F. Rahardjo (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2009)
The research aimed to describe diet composition of Thynnichthyes polylepis. The diet compositions of population from two sites (Mentulik and Simalinyang) in floodplain river of Kampar Kiri, were compared according to the month. Fishes were captured using experimental gillnet and trap. For food habits analysis, the index of preponderance method was used. The collections were performed monthly from July to December 2008, where the stomach contents of 479 specimens were assessed. Prey items of T. polylepis were basically composed of phytoplankton and zooplankton, especially Cocconeis, Nitzschia, Navicula, Cyclotella, Pleurotaenium, and Testudinella. At site Mentulik, the most common items were Cocconeis, Nitzschia, and Navicula. Conversely, at site Simalinyang, Cocconeis, Pleurotaenium, and Nitzschia more representative. In general, main food of fish origin showed the highest index values at Mentulik, whereas at Simalinyang. The composition of items varied monthly, especially at Simalinyang. Food habits of fish may be flexible according to resource availability in spatial and temporal variation.